Armed activities on the territory of the Congo before the Arusha Court or the delicate question of Rwanda’s international responsibility in the armed conflict in the Democratic Republic of Congo - MAIA, Catherine; AKPE, Aklesso Jacques (Revista Jurídica Portucalense, 2025)
On 21 August 2023, the DRC filed an application against Rwanda with the African Court on Human and Peoples’ Rights, marking the first inter-State case before the court. The DRC accuses Rwanda of massive violations of human rights and international humanitarian law, including by supporting the M23 rebel group. This conflict, rooted in ethnic and geopolitical tensions, is part of a long series of disputes involving the two states. In the absence of a binding decision by the International Court of Justice on this issue, the African Court will have to rule on Rwanda’s responsibility and its compliance with the prohibition on the use of force. Its judgment could set a precedent and redefine regional dynamics in terms of peace and security.